The Influence of Original Local Government Revenue (PAD), Population, and Gross Regional Domestic Product (GRDP) on Regional Expenditure in Kerinci Regency - Sari, Dwi Rahmita; Rahayu, Sri; Wiralestari, Wiralestari; Arum, Enggar Diah Puspa (Asian Journal of Applied Business and Management, 2024)
Regional Expenditure is a crucial component in regional budget planning, functioning to enhance public services and regional development. Regional Original Revenue (Pendapatan Asli Daerah or PAD) serves as one of the funding sources for the region, population size reflects the needs and distribution of resources, and the Gross Regional Domestic Product (GRDP) indicates the economic potential of the area. This study aims to examine the influence of Regional Original Revenue (PAD), population, and GRDP on regional expenditure in Kerinci Regency. Utilizing secondary data obtained from the Central Statistics Agency (BPS) of Kerinci Regency over the past ten years, from 2014 to 2023, this research employs a quantitative approach by applying a multiple linear regression model to identify the relationships between independent variables (PAD, population, and GRDP) and regional expenditure as the dependent variable. The results indicate that Regional Original Revenue, population, and GRDP have a significant impact on regional expenditure.